Funk this [compact disc] - Khan, Chaka (Burgundy Records : Distributed in the USA by Sony BMG Music Entertainment, 2007)
R&B vocalist Chaka Khan performs thirteen songs, including "Back in the Day," "Castles Made of Sand," and "You Got the Love."